New Method of Fabrication of Fe80Cr20 Alloy: Effect of its Technique on Crystallite Size and Thermal Stability - Dafit Feriyanto; Supaat Zakaria (International Journal of Advanced Technology, 2020)
This paper focuses on the effect of the new method on the crystallite size and thermal stability of Fe80Cr20 alloy powder. Generally, the ball milling sample and ultrasonic technique sample have dissatisfaction result when applied at high temperature. In addition, the combination of both techniques not yet carried out. Therefore, this study aim to investigate an appropriate technique to produce smallest crystallite size in order to improve the thermal stability. The new method of mechanical alloying (mill) and ultrasonic technique (UT) were applied in order to reduce the crystallite size and improve thermal stability. The new method is called as combination treatment. This condition allows the enhancement of thermal stability of Fe80Cr20 alloy powder. In this study, mechanical alloying process was carried out by milling time of 60 hours. Then, the ultrasonic technique was performed at frequency of 35 kHz at 3, 3.5, 4, 4.5, and 5 hours. From XRD analysis, it was found that the broader peaks indicated the smaller crystallite size. It shows that the combination treatment (milled and UT) reduce the crystallite size up to 2.171 nm when mechanically alloyed for 60 hours (milled 60 h) and followed by ultrasonic treatment for 4.5 hours (UT 4.5 h). Smallest crystallite size enhance the thermal stability up to 12.7 mg which shown by TGA analysis during 1100 0C temperature operation. The combination treatment is method which is effective to fabricate Fe80Cr20 alloy powder.